THE INFLUENCE OF COMPARATIVE ADVERTISING ON PURCHASING INTENTION OF INDOMIE AND MIE SEDAAP ON BOARDING HOSE STUDENT IN MANADO - Kumenaung, Dean (Universitas Sam Ratulangi, 2014)
Marketing is one of focal point in a company whether it is a product company or a service company. In marketing there’s a tool that often used as an important element to determine a product or a brand’s offer, called the 4 Ps which stands for price, product, promotion and place. One element that puts the product into the customer’s head and also the one that stands in the way between the product and the customer is Promotion. Advertising is one of the most interactive promotion and the most common one, comparative Advertising was one of the most interesting one that can be seen in television where one product compare itself to each other. This research is using qualitative that will describe the topic and explain the result of research. The object of the research are students who live in boarding house in Manado. The purpose of this research is to identify the effect that comparative advertising of Indomie and Mie Sedaap has on the consumers. The result of the research is that comparative advertising has positive effect for people who have not develop brand loyalty and yet still effective to trigger the purchase intention of the viewers. So it is recommended for marketers to reconsider their strategy and not afraid to use comparative advertising to compete in marketing competition. Keywords: advertising, brand loyalty, purchase intention